Fluticasone furoate, umeclidinium bromide, and vilanterol as a combination therapy for chronic obstructive pulmonary disease. (2nd December 2018) - Parri, Giulia; Nieri, Dario; Roggi, Maria Adelaide; Vagaggini, Barbara; Celi, Alessandro; Paggiaro, Pierluigi
ABSTRACT: Introduction : Triple therapy with two bronchodilators (LABA plus LAMA) and an inhaled corticosteroid (ICS) is recommended for patients suffering from severe chronic obstructive pulmonary disease (COPD). Areas covered : All 12–52 week-long studies comparing triple therapy with umeclidinium (UM) added to either fluticasone furoate/vilanterol (FF/VI) or fluticasone propionate/salmeterol (FP/SAL) vs. other comparators in COPD patients of group B or D (2011 GOLD classification) were considered. When UM was added to ICS/LABA with separate devices or within a single device, triple combination was more effective than comparators (usually, ICS/LABA combinations) regarding improvements to pulmonary function, symptoms, quality of life and, in the longer studies, rate of moderate-severe exacerbations. The IMPACT study (a large trial comparing UM/FF/VI with both FF/VI and UM/VI combinations) showed that triple therapy had a greater effect compared to dual therapies in reducing the rate of moderate-severe exacerbations, improving trough FEV1 and improving quality of life. The safety profile was good, without excess cardiovascular effects or pneumonia, however, the presence of comorbidities was frequent. Expert commentary : UM/FF/VI combination represents a good option for severe COPD patients who remain symptomatic and/or with frequent exacerbations despite dual therapies. Once daily administration with a simple and effective device may increase adherence and efficacy of the treatment.